Pelatihan Dasar Investasi Saham di Pasar Modal Indonesia Beserta Fintech Pendukungnya: (Studi Kasus : Pengurus PKK dan Karang Taruna Desa Cinandang, Kecamatan Dawarblandong, Kabupaten Mojokerto) - Verlandes, Yuliasnita; Fitri Isnaini, Nurdiana; Hadi Purnomo, Agus; Heru Dwihandoko, Toto (Fakultas Ekonomi Universitas Islam Majapahit, 2024)
The Covid 19 pandemic that has spread to Indonesia sice the beginning of 2020 has dramatically effected various sectors of human life. One of the sectors most effected is the economic sector. Difficult economic conditions increase public awareness of the importance of owning investments. One type investment widely looked at by the public is a stock investment in the Indonesian Capital Market. Verious supporting application servuces and educational content related to stock investment also continue to increase producyion. One rapidly growing service is fintech (financial technology) wich can be used as an investment medium. However, because so many options are available, people have difficukty choosing suitable media and tools. A few people are even ensnared by “profits anywhere” due to a lack understanding regarding investment that comply with OJK regulation. Therefore education abaout stock investment needs to be supported by understanding various safe options and can be option for investing. Therefore, it is necessary to carry out community service activites related to basic training on stock investment in the Indonesian Capital Market long with supporting fintech supervised by the OJK. The ouotput of this activity is training services to increase public knowledge about the importantce of investment and fintech options that can be used to invest safely.